2023
DOI: 10.3389/fimmu.2023.1132719
|View full text |Cite
|
Sign up to set email alerts
|

Association of atopic dermatitis with autoimmune diseases: A bidirectional and multivariable two-sample mendelian randomization study

Abstract: BackgroundObservational studies have suggested the association between atopic dermatitis (AD) and the risks of autoimmune diseases. It is still unclear, however, whether or in which direction causal relationships exist, because these associations could be confounded.ObjectivesOur study seeks to assess the possibility of AD as a cause of autoimmune diseases, and to estimate the magnitude of the causal effect.MethodsTwo-sample mendelian randomization (MR) analyses were performed using genome-wide association stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…This step aimed to screen for common risk factors before proceeding to the MVMR analysis. Considering the evidence level of observational studies, MR analysis, and the superiority of MVMR (Zhou et al, 2023), results of this study are influenced by fewer confounding factors. When cross-sectional and cohort studies found the reciprocal association between GERD and RA, those known and unknown confounding factors are often not excluded.…”
Section: Discussionmentioning
confidence: 98%
“…This step aimed to screen for common risk factors before proceeding to the MVMR analysis. Considering the evidence level of observational studies, MR analysis, and the superiority of MVMR (Zhou et al, 2023), results of this study are influenced by fewer confounding factors. When cross-sectional and cohort studies found the reciprocal association between GERD and RA, those known and unknown confounding factors are often not excluded.…”
Section: Discussionmentioning
confidence: 98%
“…We did not use proxies to replace missing outcome data. 20 In addition, we estimated the F-statistic (F = beta 2 /se 2 ) for each SNP to assess its power, and SNPs were removed if the F<10. 21 We only used SNPs available for all traits analyzed as IVs to maintain consistency.…”
Section: Methodsmentioning
confidence: 99%
“…We categorized six ADs into groups based on connective tissue disease, in ammatory bowel disease, and thyroid disease, conducting MVMR1 to discern the independent effects of each AD on IA. Additionally, MVMR2 was executed for each exposure, encompassing alcohol consumption, smoking, and systolic blood pressure, to avoid the in uence of confounding factors [15]. To further fortify our analysis, a reverse MR was conducted to counteract the potential effects of reverse causality.…”
Section: Methodsmentioning
confidence: 99%